MICROBIOLOGICAL JUSTIFICATION OF PERSPECTIVES OF USE THE MAGNESIUM ALLOY DOPED WITH SILVER IN SURGICAL PRACTICE - Черный, Вадим; Полищук, Наталья; Кирик, Дмитрий (SWorldJournal, 2021)
Modern surgical practice requires the use of medical materials that could prevent the development of purulent-inflammatory infectious conditions of the surgical field. A promising area is the use as implants or suture material of magnesium alloys doped w